(untitled) (Bangladesh Journal of Neuroscience, 2014)
There are many predictors of poor functional outcome in stroke survivors. Need of caregivers training to address the discharged patients for their home care management is often overlooked. Early discharge, lack of post-acute management facilities including home or community based services are other important predictors of poor functional outcome. Most of the patients are discharged home directly from hospital neurology unit after acute care management for inability to pay hospital costs. Rich patients who reside in the city can afford to receive treatment from trained nurse or physiotherapist at home but poor patients go home without any preparation for home care management of the patients. Hospital based rehabilitation management of stroke survivors are scarcely available in our country but thousands of inadequately treated patients are discharged home without any training to the caregivers. They come back to the outpatients department for next visit with multiple complications. This review article tried to find out the need and impact of caregivers training on outcome of stoke survivors. Bangladesh Journal of Neuroscience 2014; Vol. 30 (1): 50-52